Studi Profil Metabolit Pada Organ Tikus Hasil Uji Toksisitas Sub Kronis Ekstrak Etanol 70% Daun Justicia Gendarussa - Nur Irhamni Sabrina; Luthfiatu Kanina; Bambang Prajogo EW; Retno Widyowati; Suciati Suciati (Jurnal Serambi Engineering, 2023)
AbstractJusticia gendarussa Burm.f has been traditionally used as male contraceptionin in Indonesia. Gandarusa leaves contain gendarusin A which has potential as an antifertility agent. To prove that gandarusa leaves are safe to use as a male contraceptive, a subchronic toxicity test was carried out on this plant. Acute and subchronic oral toxicity studies of Justicia gendarussa Burm.f in rats were performed in the previous study in order to evaluate its safety. The aim of this study is to identify the metabolite profile of rat organ results of their subchronic toxicity test. Seven organs of rat such as kidney, hepar, testis, limph, instestine, lung, and heart were extracted using methanol and their profile metabolites were identified using UHPLC Vanquish Tandem Q Exactive Plus Orbitrap HRMS by positive and negatif mode. The results showed that all sampels contain 22 compounds from the positive ionization mode and 35 compounds from the negatif ionization mode. Compounds identified from the positive mode were dominated by amino acid groups, then compounds identified from the negatif mode were dominated by fatty acids and their derivatives. There were 35 metabolites that identified from the organ samples of the rat resulting subchronic toxicity test using the UHPLC Vanquish Tandem Q Exactive Plus Orbitrap HRMS method.Keywords: Justicia gendarussa Burm.f, rats, organ, metabolite profile